Validity of Nursing Outcomes Classification health promotion behavior scale in college students - Haylla Simone Almeida Pacheco; José Wicto Pereira Borges; Angelina Monteiro Furtado; Malvina Thais Pacheco Rodrigues; Márcio Dênis Medeiros Mascarenhas; Leandro Cardozo dos Santos Brito; Raquel Sampaio Florêncio
ABSTRACT Objective: to verify the reliability and validity of the health promotion behavior scale, of the Nursing Outcomes Classification, in university students. Method: methodological study carried out with 324 university students from a federal institution, based in a city in the Northeast of Brazil. Internal consistency was verified using Cronbach's alpha and item-total correlation. Validity was performed through exploratory factor analysis via main components. Results: the scale showed a Cronbach's alpha of 0.83, showing good reliability. The item-total correlations remained above 0.3 for most items, only items 01, 13, 19 and 20 were below this mark. In the exploratory factor analysis, two components were extracted whose variances explained 44.54% of the instrument's composition. Conclusion: the health promotion behavior scale showed good reliability and validity, demonstrating that it can be applied to the population of university students.